2012
DOI: 10.2169/internalmedicine.51.6434
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Comorbidity on the Prognosis of Acute Lung Injury and Acute Respiratory Distress Syndrome

Abstract: Objective We conducted a retrospective study assessing the relationship between comorbidity, using the Charlson Comorbidity Index (CCI), and the prognoses of acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) patients. Methods We analyzed the data of 47 patients with ALI and ARDS who were admitted to our center between April 2004 and July 2009. The patients were classified into 2 groups (survival and non-survival) 3 months after diagnosis, and demographic and clinical characteristics were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
3
18
0
Order By: Relevance
“…Understanding the early inflammatory changes triggered by different V T in healthy lungs, and the relationship of these changes with ventilatory parameters, may help identify injurious pulmonary insults and susceptible individuals. This knowledge may complement recently developed risk scores for predicting ARDS 1519 or postoperative pulmonary complications 13,20 in their goal of early detection and prevention of lung inflammation.…”
Section: Introductionmentioning
confidence: 90%
“…Understanding the early inflammatory changes triggered by different V T in healthy lungs, and the relationship of these changes with ventilatory parameters, may help identify injurious pulmonary insults and susceptible individuals. This knowledge may complement recently developed risk scores for predicting ARDS 1519 or postoperative pulmonary complications 13,20 in their goal of early detection and prevention of lung inflammation.…”
Section: Introductionmentioning
confidence: 90%
“…Understanding the early inflammatory changes triggered by different V T in healthy lungs, and the relationship of these changes with ventilatory parameters, may help identify injurious pulmonary insults and susceptible individuals. This knowledge may complement recently developed risk scores for predicting ARDS [15][16][17][18][19] or postoperative pulmonary complications 13,20 in their goal of early detection and prevention of lung inflammation.…”
Section: Introductionmentioning
confidence: 92%
“…Reports have revealed that smoking is a risk factor that adversely affects the incidence and prognosis of acute lung injury and other respiratory complications in the peri-operative and ICU settings [25][26][27][28][29][30][31].…”
Section: Post-operative Pulmonary Complications In Smokersmentioning
confidence: 99%